Karakteristik mutu fisik, kimia dan umur simpan beras analog dari campuran tepung ubi jalar ungu, jagung dan sagu - Feri Kusnandar; Faleh Setia Budi; Dias Indrasti; Nur Annisa; Kezia Grace Abraham; Azizah Tsaniya Fasya; Yane Regiyana; Slamet Budijanto (AGROINTEK, 2024)
Flours made from a mixture of purple sweet potato, corn, and sago have potential use in producing analog rice. The desired analog rice should contain good nutritional value, bioactive components, and have a long shelf life. The aim of this study was to evaluate the physicochemical characteristics of analog rice made from these mixed flours and to determine its shelf life. To produce the analog rice, a mixture of 2700 g purple sweet potato flour, 2700 g corn flour, 600 g sago flour, and 120 g glycerol monostearate was used with a twin-screw extruder. The resulting analog rice was analyzed for its chemical composition, total phenolic and anthocyanin content, antioxidant capacity, and shelf life using the critical moisture content method. The analog rice was found to be high in carbohydrates as the main component (81.1%) and contained a total phenolic content of 75.0 mg/100g, anthocyanin content of 19.28 mg/100g, and antioxidant activity of 54.66%. The natural purple color of the rice analog was attributed to the presence of anthocyanin (L= 36.7, a=6.54; b=3.05). When stored in polypropylene packaging at a temperature of 30°C and relative humidity (RH) of 75%, the shelf life of the analog rice was found to be 6.0 months. Different storage conditions and packaging types resulted in varying shelf-lives.